Krampfanfall nach Fehlgebrauch von Tramadol = Seizure following misuse of tramadol - Schmitt, Georg; Skopp, Gisela (Rechtsmedizin, 2016)
BackgroundSeizures following uncontrolled ingestion of tramadol are a rare occurrence.ObjectiveThis article reports the case of a traffic accident caused by a brief episode of tonic-clonic seizure, which was confirmed by witnesses.Material and methodsThe blood serum analysis revealed serum concentrations of tramadol and O-desmethyltramadol of 2780 and 746 ng/ml, respectively and additional drugs could not be detected.ResultsAlthough tramadol has become one of the most widely prescribed opioids, the mechanisms underlying its seizurogenic effects have not been fully elucidated. The risk seems to increase with an increasing dose and time of administration although blood tramadol concentrations were not found to be associated with seizures. Data on the incidence of seizures are insufficient.ConclusionThe seizure in the presented case could only be confirmed by the detailed description from third parties.
Gesehen am 11.12.2018